Evaluation of the nonalcoholic fat liver disease fibrosis score for patients undergoing bariatric surgery - Pimentel,Silvania Klug (2010)
CONTEXT: Morbidly obese patients have an increased risk for nonalcoholic fat liver disease. Its severe form, nonalcoholic steatohepatitis may cause liver fibrosis. The diagnosis of advanced fibrosis has great value during the pre operative evaluation for bariatric surgery. Currently, liver biopsy is the gold standard for diagnosis of liver fibrosis. OBJECTIVE: To evaluate the nonalcoholic fat liver disease fibrosis score in morbidly obese patients undergoing Roux-en-Y gastric bypass in our population. METHODS: One hundred fifty-eight morbidly obese patients that had undergone bariatric surgery were included. Age, body mass index, hyperglycemia, platelet count, albumin and AST/ALT ratio were applied to the score formula. Scores above 0.676 were indicative of advanced liver fibrosis and scores under -1,455 absence of advanced liver fibrosis. These scores were compared to liver biopsy findings. RESULTS: The presence of advanced fibrosis could be diagnosed with good accuracy, with a positive predictive value of 83.7%. The score had a higher accuracy to exclude advanced fibrosis with a negative predictive value of 97%. Twenty-five patients (16%) had scores between the cutoffs points and were identified as indeterminate. The score sensibility and specificity was 83% and 97% respectively. CONCLUSIONS: The nonalcoholic fat liver disease fibrosis score has high accuracy to identify and exclude advanced liver fibrosis in morbidly obese patients subjected to bariatric surgery.